Enhancing Religious Tolerance through Educators’ Behaviors - Gunawan, Indra; Saetban, Anton; Faiz, Aiman (JURNAL PENDIDIKAN ILMU SOSIAL, 2019)
Indonesia is one of the states with the greatest diversity in the world. One form of diversity is related to the choice of individuals in choosing religious beliefs. In this case, religious tolerance is a key mediation to realize the nation's ideals of unity. The religious harmony of life is an essential part of ensuring national unity. A tolerant attitude should be built through the active participation of educators in every educational environment to achieve the ideals of Pancasila, and the spirit of "Bhineka Tunggal Ika" (unity in diversity) as the noble aim of the founding fathers for the unity of the Indonesian nation.